(untitled) (International Journal of Physiology, 2019)
Introduction Obesity is associated with marked cardiorespiratory changes. In obese individuals there occurs an increase in heart rate, systolic blood pressure and cardiac output up to 15%. These changes are thought to occur as a result of changes in autonomic activity. Among the available noninvasive techniques for assessing autonomic status, heart rate variability has emerged as a simple non-invasive method to evaluate sympatho-vagal balance. Materials and Method Heart Rate Variability analysis was done in 30 young obese individuals and compared with 30 age and gender matched individuals with normal BMI Results In obese individuals, the SDNN was significantly higher than in controls. LF and LF/HF values of obese individuals were significantly higher than those of controls but their HF values were lower. Conclusion HRV analysis shows sympathetic overactivity and parasympathetic blunting in young obese individuals.